Key for the species of the genus Rosa (Rosaceae) which occur in the communities of Pruno-Rubion ulmifolii in the Iberian Peninsula - Arnáiz, C.; Loidi, J. (Lazaroa, 2014)
A dichotomous key based on easily recognizable features for seventeen Rosa species present in communities of the aliance Pruno-Rabion ulmifolii (Prunetalia) in the Iberian Peninsula is presented.